Analisis Penerapan Strategi Harga Dan Diferensiasi Produk Dalam Keunggulan Bersaing Di Sekolah Alam Purwakarta - Rahma Ngaisah; Rina Nurhayati; Ayi Nurbaeti (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2020)
The purpose of this research are to know the price strategies of competitive advantaes that is adopted at the Sekolah Alam Purwakarta and how Sekolah Alam Purwakarta presents products differentiation in provding education that is conceptualized according to student needs. The approach of this research uses a qualitative approach. Which is a descriptive study and tends to use analysis with an inductive approach. The competitive advantage strategies applied for educational institutions through the Sekolah Alam Purwakarta pricing strategy involves various parties from Yasasan, Schools, and Parents, and has a pricing policy that is in accordance with government policy, a pricing channel that involves committees as parents' representatives , a clear factor so that price changes can be accounted for, as well as obstacles that have a solution. The second adventage are presenting product differentiation in the form of typical programs. That are morning activity, outbond, home visit, bussines day, fun advanture (camping/ tracking), farming, cooking spesial events, experiments, aquaplays, educational visits, lunches, midday prayers, suttle using companion teacher, trash bank, interships, and backpackers.